Effects of restoration years on soil nitrogen and phosphorus in inland salt marshes - Dandan Zhao; Daiji Wan; Jian Yang; Jiping Liu; Zhicheng Yong; Chongya Ma (PeerJ, 2024)
Inland salt marsh wetlands have very important ecological functions in semi-arid areas. However, degradation and soil desertification have impacted these areas, making it necessary to study the impact of wetland restoration years on the soil quality of salt marsh wetland. We used remote sensing methods, field surveys, and inquiries to examine the seasonal profile effects of two-, four-, and six-year restoration periods on total nitrogen (TN), total phosphorus (TP) and the ratio of nitrogen to phosphorus (N:P) in P. australis and S. triqueter wetland natural states. Our results showed that soil TN in P. australis wetland in restored conditions was higher than that in natural conditions. The average soil TP of the S. triqueter wetlands at 0–10 cm, 10–20 cm, 20–30 cm, and 30–40 cm layers was 0.36 g/kg, 0.31 g/kg, 0.21 g/kg, and 0.17 g/kg s in September, respectively. The soil TP of the S. triqueter wetland increased slightly over the entire growing season. The restoration years had a great influence on the soil TP of the S. triqueter wetland from May to July. The soil TN in the P. australis wetland was almost restored to its natural condition in each layer during the six-year restoration period. The soil TP of the S. triqueter wetland was higher in the restored two-year period and showed a decreasing trend with an increased soil depth. Our conclusions can significantly guide the restoration of inland salt marsh wetlands.